Remarks about Lp — Lq estimates for solutions of the Klein — Gordon equations - Markovsky , A. I. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
We clarify some difficulties in the proofs of estimates, which were established earlier, in the paper by Marshall, Straus and Wainger devoted to the Lp — Lq estimates of solutions to the Klein — Gordon equation.